Air quality in library: assessment of pm10 and pm2.5 concentrations at different floor levels of USM Health Campus’s Library - Nordin, Siti Mariam (Universiti Sains Malaysia, 2016)
Library is one of the most frequent visited place by university students everyday. Many students favor to spend their time in library. Indoor exposure to air pollutants may occur in library. The purpose of this study is to assess the indoor air quality (IAQ) in library at USM Health Campus, Kota Bharu, Kelantan. The comparison of PM|0 and PM25 concentrations between floor levels of library was determined. This study was also conducted to obtain the associations between PMio and PM25 concentrations with number of occupants, temperature, relative humidity and total number of books. Particulate matter concentrations were measured at library by using Handheld 3016 IAQ Particle Counter. The data was collected for eight hour for each floor with five minutes time interval. Based on Kruskal Wallis test, there was significant differences of PM2.5 and PMio concentrations between floor levels (p<0.05). Number of occupants had significant associations with PM2.s concentration through Spearman Correlation test (p<0.05). Furthermore, there was also a significant association between temperature and relative humidity with PMio and PM2.s concentrations. However, the correlation between particulate matter concentration with temperature and relative humidity were poor (r-PMio=0.22, r-PM2s=-0.15; /--PMio=-0.17, r-PM2 5=0.2). Number of books and different floor surface area of library can be contributing factor too. In conclusion, regular cleaning and housekeeping activities in library need to be done to minimize IAQ problems and to provide a healthier indoor environment.